MASALAH RENDAHNYA ICT LITERACY DALAM PEMBELAJARAN AKUNTANSI DI ERA TEKNOLOGI INFORMASI - B. Indah Nugraheni (Jurnal Pendidikan Akuntansi Indonesia, 2006)
MASALAH RENDAHNYA ICT LITERACY DALAM PEMBELAJARAN AKUNTANSI DI ERA TEKNOLOGI INFORMASIIn this current information and technology era, Information and Communication Technology (ICT) has unavoidably become an integral part of human life, including that in education especially in learning activities. Based on many studies, ICT, especially computer technology, can make learning processes more effective and efficient. This also happens in accounting learning processes. Indeed, the use of computer technology (multimedia) in accounting learning activity is needed because it will solve difficulties faced by students in their attempt to understand the concept of accounting. Consequently both teachers and students need to have ICT literacy. Unfortunately, lack of ICT literacy that education practitioners are coping with has still become a problem in the implementation of information technology in accounting learning. Because of the urgent need of ICT literacy for instruction and lack of ICT literacy, there is an immediate need to have some efforts to overcome that problem. Those efforts are: (1) developing curriculum that includes ICT literacy for primary and secondary schools, as well as for schools of  teacher education (previously a university’s faculty of teachers training and education); (2) preparing the human resources, i.e., teachers, through training; (3) providing schools with computer facilities (including hardware and software) and the access to the internet, (4) designing and developing digital libraries; (4) developing ICT centers and maximizing their functions to generate ICT programs (software); (5) developing network; and (6) increasing both teacher’s and learners’ consciousness  of the ICT and its urgency as the learning media and resources. Kata kunci : ICT and ICT literacy, ICT in curriculum design, human resources development, accounting learning